Evaluation of Implementing Status of Diploma Nursing Curriculum in Bangladesh (Bangladesh Journal of Medical Education, 2012)
This descriptive type of cross-sectional study was conducted to evaluate the implementing status of diploma nursing curriculum in Bangladesh according to teachers' and students views along with four specific objectives. The study was conducted at different government diploma nursing institutes of Bangladesh within July 2009 to June 2010. Teachers & students of different diploma nursing institutes were the study population. Out of them as per the inclusion and exclusion criteria data were collected by simple random sampling. Self-administered structured questionnaire was used to collect data. Sample size was 1107 out of which 103 teachers and 1004 students. Study revealed that out of 1107, 626 (56.8%) respondents expressed that the present diploma nursing curriculum averagely will be able to fulfill the demand of the nursing profession. Most of the respondents 1001 (90.4%) expressed their opinion that the present diploma nursing curriculum should be changed. 1088 (98.3%) responded negatively that they do not get books as per need of the curriculum. 1084 (97.9%) respondents replied negatively that they do not have sufficient teaching staff for implementing present diploma nursing curriculum. Around 583 (52.7%) respondents replied negatively that examination are not conducted perfectly as per the present curriculum. 667 (60.6%) respondents expressed about library, 609 (55.3%) expressed about practical classes & 785 (71.3%) viewed about clinical training at hospital for better implementation of diploma nursing curriculum. Study recommended that the ongoing diploma nursing curriculum to be reviewed, updated considering the context of the country as well as need of the country, books to be developed/written as per the demand of present diploma nursing curriculum and should make those available. For better implementation of diploma nursing curriculum it was also recommended that number of the relevant teachers at different nursing institutes to be increased & they should be oriented on revised updated diploma nursing curriculum, teaching methodology and evaluation or assessment of the students. For the improvement of present diploma nursing course admission policy, syllabus /course materials, teaching methods, evaluation/assessment, library, practical class and clinical training at hospitals to be changed and redesigned for the better interest of the country as well as for the nursing profession. DOI: http://dx.doi.org/10.3329/bjme.v1i1.12855 Bangladesh Journal of Medical Education Vol.1(1) 2010 pp.25-28